Laboratory studies on seepage and physical properties of low cost lining materials for field channels - CHINTHA C; Rengith George; Vinayak N. C; Er. Rema K.P (Guide) (Tavanur 2000 Kelappaji College of Agricultural Engineering and Technology)
Laboratory studies on seepage and physical properties of low cost lining materials for field channels
Laboratory studies on seepage and physical properties of low cost lining materials for field channels